Variable use of polyadic grooming and its effect on access to social partners in wild chimpanzees and bonobos. (October 2020) - Girard-Buttoz, Cédric; Surbeck, Martin; Samuni, Liran; Boesch, Christophe; Fruth, Barbara; Crockford, Catherine; Hohmann, Gottfried; Wittig, Roman M.
Abstract : In mammals, allogrooming is prominent in forming and maintaining social and cooperative relationships. Yet an animal's social time is constrained, which may limit its access to a large number of partners. Dunbar (1993, Behavioral and Brain Sciences, 16 (4), 681–694) proposed that human polyadic conversations, which allow access to several social partners simultaneously, evolved as a form of social grooming to circumvent this time constraint. In nonhuman primates, polyadic grooming (PG), in contrast to dyadic grooming, may similarly be a time-efficient way to maintain weak social relationships with many partners which can be important for group level cooperation. It remains unknown whether PG is used to fulfil specific cooperative needs by accessing numerous weakly bonded partners and increasing the number of partners accessed per unit of time. We compared the use and effect of PG between chimpanzees, Pan troglodytes, which are highly territorial and collaborative (especially males), and bonobos, Pan paniscus, which are less territorial and collaborative and in which females are the main co-operators. We carried out focal grooming observations in one bonobo and two chimpanzee communities in the wild. As predicted, chimpanzees engaged in more PG than bonobos. Surprisingly, males engaged in PG more than females in both species. While chimpanzees accessed more partners per minute of grooming than bonobos via dyadic grooming, PG increased the number of partners accessed per minute only in bonobos. Finally, chimpanzees primarily used PG with individuals who were close in rank and frequent grooming partners, whereas bonobos used PG with individuals who were distant in rank, close party associates and frequent grooming partners. We suggest that bonobo males use PG to enhance conspecific social tolerance and mate choice. The overall higher rate of PG in chimpanzees suggests that between-group competition may promote polyadic affiliation, which possibly reinforces group cohesion and coordination. Highlights: Polyadic grooming (PG) is hypothesized to promote efficient access to many partners. Territorial wild chimpanzees engaged more in PG than nonterritorial wild bonobos. PG increased the efficiency of access to partners in bonobos but not in chimpanzees. Both chimpanzees and bonobos primarily used PG with frequent grooming partners. Between-group competition may promote polyadic forms of affiliations.